Digitalized Arabic Language Environment in Kampung Arab Al-Azhar Pare - Nurul Hanani; Faiqoh, Putri Kholida; Hamida Gadoum; Anggi Nurul Baity; Yessica Tiara Renata (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2025)
The Arabic language learning environment is evolving not only in physical (offline) settings but also in digital (online) spaces. One of the institutions fostering an Arabic-speaking environment is Kampung Arab Al-Azhar Pare. This study aims to describe and analyze the Arabic language learning process and the design of a digital Arabic environment in Kampung Arab Al-Azhar, located in Pare, Kediri, East Java. The research employs a qualitative descriptive approach, using data collection techniques such as observation, interviews, and documentation. Data were gathered following Lincoln and Guba's model through participant observation, systematic interviews with key stakeholders, and document analysis. The findings indicate that Kampung Arab Al-Azhar offers various intensive online Arabic learning programs that adhere to the principles and conditions necessary for creating a conducive language environment. The implementation of institutional policies, teacher recruitment, and digital learning integration has been carried out effectively. However, a notable challenge remains: the current understanding and use of the Learning Management System (LMS) do not fully reflect its potential as a critical component of digital learning. This limitation may hinder the optimal achievement of learning outcomes.